Respiratory Health Problems Among Spinning Mill Workers - Zaman, Md Ahsan uz; Chowdhury, Md Sunyet Alam; Hossain, Irin (Journal of Preventive and Social Medicine, 2025)
Background: Occupational respiratory diseases are significant public health concerns, particularly in the textile industry, where cotton dust exposure in spinning mills often leads to respiratory problems. Workers in spinning mills are at high risk of developing symptoms such as cough, breathlessness, and chest tightness due to prolonged exposure to cotton dust. Methods: This cross-sectional study was conducted from January to December 2021 at Top Spinning Mill, located within Alauddin Textile Mill, Tangail district. A purposive sampling method was used to select 278 respondents directly involved in the spinning process, stratified by working sections. Participants included male and female workers aged 19 years or older with at least one year of employment. A semi-structured questionnaire based on the ATS standard questionnaire was used to collect data, alongside spirometry to assess lung function and PM2.5 and PM10 measurements across sections. Results: Among the 278 respondents, 68% were female, with a mean age of 32.96 ± 10.67 years, a mean income of 6813.92 ± 3115.00 BDT, and an average employment duration of 6.38 ± 4.14 years. Smoking prevalence was 11.9%. Nearly 46% reported respiratory health problems, with cough (43.2%) being the most prevalent symptom. Spirometry revealed 12.2% had reduced FEV1, while 10.8% showed a reduced FEV1/FVC ratio. PM2.5 and PM10 levels were highest in the Blow Room. Significant associations were found between respiratory health problems and age, working section, and employment duration. Conclusion: High respiratory health issues were observed among spinning mill workers, particularly in sections with elevated PM2.5 and PM10 levels. Health awareness programs and improved workplace supervision are recommended to mitigate respiratory problems and create a safer working environment. JOPSOM 2024; 43(2): 77-82